(3GdaQhSjI HQSe GdLgGO heG CYO Gddg ddeLGgOjf ef GdYHGOs
(3ChdgG (B:s
(3JHOC HGSe Gdedc GdeXaQ s
(3BNQgG (B:s
(3JfJgi HPcQ GdSWGf GdfGUQ eMeO Hf bdGhhf (B( (3CMOGK (B703(3g` (B) s
(3Vef eLehY , JQJjHgG (B: (3ef U (B71s
(3HBNQgG ehLRg ai JhGQjN SdGWjf eUQ GdeeGdjcs
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B905 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B25 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs